A comparative study of traditional high-fidelity (manikin-based) simulation and virtual high-fidelity simulations concerning their effectiveness and perception - Izabela Sałacińska; Patrycja Trojnar; Krisztina Éles Gebriné; Viktória Törő; Viktória Törő; Attila Sárváry; Paweł Więch (Frontiers in Medicine)
IntroductionMedical simulation has become an integral part of medical student education. There is a limited body of literature comparing virtual and high-fidelity simulation in terms of effectiveness and student perception.MethodsA total of 130 medical students at the University of Rzeszów participated in this cross-sectional study. The respondents were divided into two groups: students who completed a selected scenario using a virtual patient (Body Interact) and students who completed a scenario using traditional high-fidelity (manikin-based) simulation (HFS). After completing the scenario, students filled in the following questionnaires: the Simulation Design Scale (SDS), the Educational Practices Questionnaire (EPQ), the Student Satisfaction and Self-Confidence in Learning Scale (SSCL) and a customized survey questionnaire.ResultsThe study found no significant difference in the effectiveness of HFS between students exposed to either type of simulation. Detailed analysis within specific categories – problem-solving, teamwork, and active learning – also showed no significant differences between virtual and traditional HFS. Furthermore, there were no notable differences between virtual and traditional simulations regarding specific aspects such as satisfaction with learning, self-confidence in learning, and expectations. However, within the virtual simulation group, females rated active learning significantly higher. Students aged 24–33 rated satisfaction with learning, self-confidence, overall effectiveness and perception of HFS, problem-solving, and active learning more favorably. Additionally, the levels of perceived effectiveness and satisfaction of higher years students with HFS increased.ConclusionVirtual patient simulation and traditional HFS foster the development of practical skills, as well as soft skills of medical students in challenging situations.